Pelatihan ChatGPT dan Manajer Referensi Mendeley untuk Meningkatkan Literasi Akademik Digital Mahasiswa FAI Universitas Nurul Jadid - Moh. Rofiki; Eka Diana; Saadul Latifah; Nadia Kholifatur Khoir; Nur Atika Hasani (Indo Publishing, 2025)
The Faculty of Islamic Studies at Nurul Jadid University has a vision to become a leading institution based on Islamic boarding schools that is adaptive to technological and scientific developments. However, in academic practice, there is still a low level of digital academic literacy among students, particularly in scientific writing and reference management. Students tend to be unfamiliar with the use of supporting technologies such as ChatGPT and the Mendeley reference manager. Yet, these technologies hold significant potential in enhancing students' academic productivity and quality. Given this situation, this community service program was designed to improve students' ability to write scientific articles efficiently and accurately through training in the use of ChatGPT and Mendeley. The implementation method includes stages of needs-based planning, theoretical and practical training, as well as continuous monitoring and evaluation. The results of the activity showed a significant improvement in students' understanding and skills in digital-based scientific writing, as well as high enthusiasm from the participants. However, some technical challenges and differences in students' initial digital literacy levels remain as obstacles. Therefore, follow-up actions are needed through continuous mentoring and the integration of this training into the curriculum to ensure its benefits are widely and sustainably felt within the academic environment.